MODERN APPROACHES TO THE ORGANIZATION OF DRUG PROVISION FOR HIV-INFECTED PATIENTS IN KUZBASS - Андрей Георгиевич Петров; Ольга Владимировна Хорошилова; Виктор Андреевич Семенихин; Сергей Николаевич Филимонов; Наталья Степановна Черных (Медицина в Кузбассе)
The health of the population of the Russian Federation and Kuzbass is the most important national, national, medical and social problem. In recent years, HIV infection has been a leading cause of infectious diseases. In this regard, the organization of drug provision for HIV-infected patients is of particular importance. The aim of the study – the study of the organization of drug provision for HIV-infected patients in Kuzbass. Materials and methods. Scientific approaches were used as research methods: regional, systemic, structural and functional; methods: historical, logical, content analysis, sociological, statistical, modeling and forecasting, etc. The results and their discussion. In the modern world, the problem of the spread of HIV infection remains urgent and requires close attention. In Kuzbass, as in other regions of Russia, there is an organization of drug provision for HIV-infected patients. It includes a number of measures aimed at ensuring the availability of necessary drugs and monitoring their use. In this regard, the study of scientific approaches to the concept of specialized pharmaceutical care (AF), including the organization of drug care based on sociological research, shows that it is necessary to develop a modern system of personalized SFP. This is necessary to improve the quality and identify the main directions in optimizing specialized pharmaceutical care for the population with HIV infection. Conclusion. The organization of drug provision for HIV-infected patients in Kuzbass is a comprehensive system based on the principles of accessibility, quality, effectiveness, individual approach and cooperation with public organizations. Government programs and projects play an important role in the implementation of this system and contribute to improving the situation with the provision of medicines to HIV-infected patients.